Measurement properties of adult quality-of-life measurement instruments for eczema: a systematic review - Heinl, Daniel; Prinsen, C. a. C.; Deckert, S.; Chalmers, J. R.; Drucker, A. M.; Ofenloch, Robert; Humphreys, R.; Sach, T.; Chamlin, S. L.; Schmitt, J.; Apfelbacher, C. (Allergy, 2016)
Background The Harmonising Outcome Measures for Eczema (HOME) initiative has identified quality of life (QoL) as a core outcome domain to be evaluated in every eczema trial. It is unclear which of the existing QoL instruments is most appropriate for this domain. Thus, the aim of this review was to systematically assess the measurement properties of existing measurement instruments developed and/or validated for the measurement of QoL in adult eczema. Methods We conducted a systematic literature search in PubMed and Embase identifying studies on measurement properties of adult eczema QoL instruments. For all eligible studies, we assessed the adequacy of the measurement properties and the methodological quality with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. A best evidence synthesis summarizing findings from different studies was the basis to assign four degrees of recommendation (A-D). Results A total of 15 articles reporting on 17 instruments were included. No instrument fulfilled the criteria for category A. Six instruments were placed in category B, meaning that they have the potential to be recommended depending on the results of further validation studies. Three instruments had poor adequacy in at least one required adequacy criterion and were therefore put in category C. The remaining eight instruments were minimally validated and were thus placed in category D. Conclusions Currently, no QoL instrument can be recommended for use in adult eczema. The Quality of Life Index for Atopic Dermatitis (QoLIAD) and the Dermatology Life Quality Index (DLQI) are recommended for further validation research.
First published: 13 November 2015
Gesehen am 12.05.2020